The Roles of Financial Reporting and Self-Concept of Cooperative’s Managers in Using Accounting Information - Yustina Triyani; Masripah - (Journal of Management and Leadership, 2019)
A lot of cooperatives do not use adequate accounting information in preparation of financial reporting. Lack of knowledge and understanding in accounting principles, also a low level of selfconcept of the employees are the possible main reasons behind it. Thus, this study aims to find evidence on the effect of accounting knowledge and self-concept of cooperative managers on the use of accounting information. The object of this research is the managers of the cooperative members Dekopinda in North Jakarta, which consists of 100 respondents from 49 cooperatives. The methods of this research are field survey and data analysis using validity test, reliability, classical assumption and regression test. The test results show that all the data pass the validity, reliability and classical assumption test. F test results show the number 0.001, t-test results for accounting knowledge variables obtained 0.023 and self-concept 0.031. This study concludes that there is sufficient evidence that accounting knowledge and self-concept of cooperative managers have a positive effect on the use of accounting information.